Analysis Of Influence Of Directive Leadership Syle Career Development And Motivation Towards The Performance Of The Employees Of The Department Of Agriculture And Food The Regency Polewali Mandar Regency - Ulang, Tenri; Ruslan, Muhlis; Remmang, Hasanuddin (Indonesian Journal of Business and Management, 2018)
The influence of the leadership style of the directive, the development of a career, and motivation towards the performance of the employees of the Department of agriculture and food the Polewali Mandar Regency, (guided by Muhlis Ruslan and Frank Remmang). This research aims to analyze and test menginterpertasi; 1.) the influence of the leadership style of the directive against the performance of employees; 2) influence the development of career employees on performance; 3) influence motivation towards the performance of the employees of the Department of agriculture and food the Polewali Mandar Regency. The design in this study using the method of quantitative research using survey method. The number of samples in the study 73 people. Penelitin uses a quantitative descriptive analysis techniques were analyzed with the help of SPSS software 24. The conclusions from the results of this study are: 1) the leadership style of direktris positive effect and significance on performance clerk; 2) positive and influential career development significance against the performance of employees; 3) positive and influential significance of motivation against the performance of the employees of the Department of agriculture and food the Regency Polewali Mandar.